PHARMACY TECHNICIANS’ PERCEPTIONS OF INTERPROFESSIONAL EDUCATION: A QUALITATIVE STUDY - Fheed Saud Alrasheedi, ‏Nouf Hamad Alharbi, ‏Ahmed Abdullah Alenazy, ‏Sahar Obaid ALshammari, ‏Abdullah Hamdan Alshammeri, Sami Falah Alrowaili (Chelonian Research Foundation, 2022)
Interprofessional education (IPE) is increasingly adopted to enhance collaborative practice capabilities among healthcare students. However, literature focuses predominantly on physician and nurse experiences, with minimal evidence exploring pharmacy technicians’ perspectives. This qualitative study aimed to elicit Saudi pharmacy technicians’ perceptions regarding IPE based on participation in an interprofessional simulation course. Individual semi-structured interviews were conducted with 20 technicians. Inductive thematic analysis yielded themes around perceived value of collaboration despite reservations, opportunities to recognize profession roles, gain interactive skills, and dismantle hierarchies. However, technicians also reported feeling marginalized and that traditional asymmetric power dynamics persisted. Nuanced insights can shape more equitable, mutually beneficial IPE and collaborative practice inclusion for this integral but underrepresented group. Keywords: interprofessional education; pharmacy technicians; perceptions; interviews; qualitative